Ciri-ciri perbualan dan strategi komunikasi pemandu pelancong tempatan dalam bahasa Jepun - Mamat, Roslina; Abdul Rashid, Roswati; Abdul Halim, Hazlina; Abd Rahim, Normaliza; Mansor, Nor Shahila (Persatuan Linguistik Malaysia, 2014)
Cross cultural communication often occurs in a speech when one speaks with someone who is different in gender, language, race, religion and social status. A tour guide has to be equipped with the ability to transmit accurate information in order to create effective cross-cultural communication. Cross-cultural communication necessities a review of the characteristics of conversation and communication strategies used by tour guides. This paper examines the characteristics of conversation and communication strategy based on the context of cross-cultural communication between Japanese speaking tour guides and Japanese tourists in Kuala Lumpur. The data were collected based on the comparison between tour guides who are proficient and less proficient in Japanese language. The respondents of this study are two licensed Japanese spoken tourist guides and with permit as Japanese speaking tourist guides. The conversation recorded was between the tourist guides and Japanese tourists for two visit sessions. Both tourist guides R1 and R2 are Malay. Data were derived from two audio recordings and visual interaction between the guides and Japanese tourists while preparing the full transcription of FIT package. The findings showed that various performance types of communication strategies were performed to establish effective communication by tour guides who were less proficient in Japanese language. On the other hand, conversational strategies such as appropriate turn takings, the use of politeness forms between humor and praises were identified as strategies applied by tourist guides who were fluent in Japanese.